TANTANGAN DAN HAMBATAN DALAM PENERAPAN LITERASI NUMERASI PADA PROSES PEMBELAJARAN MENGGUNAKAN APLIKASI CANVA - Suryaningsih, Eny; Maarij, Fatkhul (Prosiding Temu Ilmiah Nasional Guru, 2023)
The development of Science and Technology (IPTEK) is growing very rapidly in line with the progress of the 4.0 era which indicates the need for the application of information technology, especially in the school environment. The aim of this research is to determine the challenges and obstacles to achieving the use of the Canva application in preparing literacy and numeracy at SMAN 25 Tangerang Regency and SMAN 11 Tangerang Regency through the process of learning activities in class 12 science. The research method used is qualitative by analyzing the results of a survey on the implementation of activities using the Canva application to increase the literacy and numeracy of students in schools according to the policies of the Banten provincial education office through webinar activities on the application of the Canva application in the learning process. The results of research from among 30 students revealed that 4 respondents were in the signal interference category which had an impact on long loading (ngelek). 5 people and those who said it was complicated/complicated/somewhat difficult, and using the Canva application was easy to understand, fun and interesting for the material being studied was 70%. To increase literacy and numeracy effectively and efficiently with the aim of improving high-level thinking abilities, it is necessary to familiarize students with the use of other applications in the learning process activities.